HOLMES, Douglas. 2014. Economy of Words: Communicative Imperatives in Central Banks. Chicago: University of Chicago Press. 280 pp. - Scoz Pasteur de Faria, Louise (Campos - Revista de Antropologia, 2016)
Resenha de Economy of Words: Communicative Imperatives in Central Banks, de Douglas Holmes, publicado em 014.